The Influence of Digital Culture, Teacher AI Competence, and Teacher Leadership on Student AI Leadership and Academic Performance at Senior High School in Muaro Jambi - Nova Triana Hakim; Hendra, Robi (FKIP Universitas Jambi, 2025)
This study examines the impact of digital culture, teachers’ AI competence, and teacher leadership on students’ AI leadership and academic performance amid digital transformation in education. Grounded in an extended Technology Acceptance Model (TAM), the research explores how these constructs interact to influence AI integration in teaching and learning. A quantitative approach was employed, with data collected from students at Senior High School in Muaro Jambi who engaged in AI-assisted learning. Using Partial Least Squares Structural Equation Modeling (PLS-SEM) for analysis, the study found that digital culture significantly and positively impacts teacher leadership, teacher AI competence, and student AI leadership, positioning digital culture as a primary enabler of technological and pedagogical innovation. However, the direct effects of teacher leadership, teacher AI competence, and student AI leadership on academic performance were positive but statistically insignificant, suggesting that their influence is mediated through pathways of leadership and competence development. These findings underscore the importance of fostering a strong digital culture for AI adoption and highlight that improvements in academic performance require sustained pedagogical alignment and implementation. This research contributes to the theoretical expansion of TAM by integrating cultural and human dimensions. It offers practical insights for educators and policymakers aiming to strengthen AI integration for educational transformation.